Refining the management of patients with hepatocellular carcinoma integrating 11C-choline PET/CT scan into the multidisciplinary team discussion. Issue 10 (October 2017) - Lanza, Ezio; Donadon, Matteo; Felisaz, Paolo; Mimmo, Antonio; Chiti, Arturo; Torzilli, Guido; Balzarini, Luca; Lopci, Egesta
Abstract : Objective: The aim of this study was to report the impact of 11 C-choline PET/CT on the management of patients with hepatocellular carcinoma (HCC) and incorporate into a refined algorithm combining diagnostic imaging and multidisciplinary team (MDT) discussion. Patients and methods: From February 2010 to February 2016, the charts of all patients discussed in the liver MDT were revised. Suspected or confirmed HCC lesions or Barcelona Clinic Liver Cancer stages A, B or C with a 11 C-choline PET/CT performed in our hospital were included in the analyses. Overall, 73 patients (male : female=59 : 14; median age: 75 years) were enrolled. Forty-two (57%) patients were newly diagnosed, whereas 31 (43%) came to our attention at disease recurrence. Seven (10%) patients were Barcelona Clinic Liver Cancer stage 0, 31 (42%) patients were stage A, 15 (20%) patients were stage B, and 18 (25%) patients were stage C. The reference standards for ultimate imaging validation were either histology or MDT consensus. A minimum follow-up of 6 months was established. Results: Overall eight (10%) patients were initially referred for chemotherapy (sorafenib), 43 (59%) for surgery, two (3%) for surgery or transarterial embolization, five (7%) for follow-up only, one (1%) for extrahepatic radiotherapy, seven (10%) for stereotactic body radiation therapy of the liver, six (8%) for transarterial embolization, and one (1%) for liver transplant. After 11 C-choline PET/CT and MDT discussion, in seven patients the diagnosis changed, in six patients the treatment was changed, and in nine patients both the diagnosis and the treatment were changed. Overall, in 30% of our patients, the diagnosis or treatment was altered on the basis of our algorithm of management. Conclusion: The incorporation of 11 C-choline PET/CT into the MDT discussion altered the diagnosis/treatment of one-third of HCC patients. We propose a novel diagnostic algorithm to be refined in referral centers for HCC management.